Pengaruh Inventory Intensity, Thin Capitalization, Current Ratio dan Pemeriksaan Pajak Terhadap Tax Avoidance : Studi Empiris Pada Perusahaan Perdagangan Besar di Kantor Pelayanan Pajak Madya Banjarmasin Periode 2020 - Muhammad Setiawan; Monica Rahardian Ary Helmina; Novita Weningtyas Respati (Edunomics Journal, 2024)
This study aims to obtain empirical evidence regarding the effect of inventory intensity, thin capitalization, current ratio and tax inpection on tax avoidance. The type of this research is associative research with a quantitative approach. The data used in this study is secondary data where the data is obtained from KPP Madya Banjarmasin. The dependent variable in this study is tax avoidance and the independent variable in this study is inventory intensity, thin capitalization, current ratio and tax inpection. The sample of this research is 81 large trading companies registered in KPP Madya Banjarmasin that have been selected using predetermined criteria. The analysis technique used in this research is multiple linier regression test. The results of this study indicate that inventory intensity, and tax inpection has positively affects on tax avoidance. Meanwhile, the current ratio does not affect tax avoidance